2009
DOI: 10.1186/1745-6215-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting of randomized controlled trials in polycystic ovary syndrome

Abstract: BackgroundInadequate reporting of randomized controlled trials (RCTs) is associated with biased estimates of treatment effects. The reporting quality of RCTs involving patients with polycystic ovary syndrome (PCOS) is unknown. The purpose of this study was to assess the reporting quality of RCTs involving patients with PCOS using a standardized tool based on the Consolidated Standards of Reporting Trials (CONSORT) statement.MethodsWe searched PubMed database for English-language RCTs involving patients with PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…This is in stark contrast to the overall landscape in the literature in which RCTs in general are being published at an approximate rate of 200 per week, according to an estimate in the year 2000; neurosurgery clearly lags behind. 26 In terms of the quality of reporting, however, similar analyses to ours have identified significant deficiencies in other specialties such as oncology, 15,24 gynecology, 21 orthopedic surgery, 5,23 and plastic surgery.…”
Section: Discussionmentioning
confidence: 66%
“…This is in stark contrast to the overall landscape in the literature in which RCTs in general are being published at an approximate rate of 200 per week, according to an estimate in the year 2000; neurosurgery clearly lags behind. 26 In terms of the quality of reporting, however, similar analyses to ours have identified significant deficiencies in other specialties such as oncology, 15,24 gynecology, 21 orthopedic surgery, 5,23 and plastic surgery.…”
Section: Discussionmentioning
confidence: 66%
“…The subgroup of high-impact journals showed even a larger proportion. A review on randomised trials in special medical fields found smaller proportions [19,20]. Surprisingly, Hopewell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the basis of our investigation is the entire picture of published reports and considerably exceeds a more or less representative random sample [11,14] or an analysis of trials regarding only a specific therapeutic area [13,19-22]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the creation of the CONSORT in 1996, studies showed that the quality of RCT reporting has improved , as it was introduced within journal guidelines. An improvement in RCT reporting has also been shown in manuscripts published after the introduction of this checklist in the medical literature . Therefore, we extracted the proportion of RCTs with low risk of bias (good internal validity) for each domain according to the Cochrane risk of bias tool for RCTs included in our review published before 1996 (the pre‐CONSORT period) and after 1996 (post‐CONSORT statement).…”
Section: Methodsmentioning
confidence: 99%